1974
DOI: 10.1007/bf00017940
|View full text |Cite
|
Sign up to set email alerts
|

Response of olive and almond orchards to partial irrigation under dry-farming practices in semi-arid regions:

Abstract: The response of elements of the water balance of olive plants grown in desert farms to partiall irrigation was investigated. A m o n g these are transpiration, leaf relative water content, the number of leaves carried by trees and the osmotic pressure of the leaf sap. The proper time for irrigation and suitable ways of its application were also studied. A method of applying subsurface irrigation, to minimize direct evaporation from the soil, is described. The results show a slight decrease in transpiration rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…The following years, trees set fruits and yield increased substantially, while annual growth rates decreased substantially, reaching their lower values six years after plantation. Similar patterns of growth were reported for almond and peach trees [31], showing optimum increases four years after plantation and high variations from year to year in response to the changing conditions and the degree of adaptation of varieties to the environmental factors and their changes. Low rates recorded for canopy and tree height after the optimum value seems to be inherent to the establishment of competition between the vegetative growth and the growing fruits, which is well-known for adult trees [3,4,7,9,24,30].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The following years, trees set fruits and yield increased substantially, while annual growth rates decreased substantially, reaching their lower values six years after plantation. Similar patterns of growth were reported for almond and peach trees [31], showing optimum increases four years after plantation and high variations from year to year in response to the changing conditions and the degree of adaptation of varieties to the environmental factors and their changes. Low rates recorded for canopy and tree height after the optimum value seems to be inherent to the establishment of competition between the vegetative growth and the growing fruits, which is well-known for adult trees [3,4,7,9,24,30].…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, from bud break to pit hardening, large amounts of assimilates are needed to supply shoots, roots, trunk, buds and the developing fruits [3,9,24,32]. A great reduction of the current vegetative growth is always recorded because the new biomass produced is mostly driven to fruits, while the previously existing shoots did not increase in biomass [4,7,31]. After this period of pit hardening, fruit size increased, while shoot development decreased noticeably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sap osmotic potential, Abd-El-Rahman et al (1966) observed a marked rise in the osmotic pressure of the olive sap throughout the dry season, exceeding the values observed in other xerophytes. Rieger (1995) also observed osmotic adjustment in expanding olive leaves, finding values of osmotic potential similar to those reported by Abd-El-Rahman and El-Sharkawi (1974). The increase in sap osmotic pressure enables the roots to extract more water when the soil dries (Abd-El-Rahman et al, 1966).…”
Section: Introductionmentioning
confidence: 63%
“…Abd-Eel-Rahman and El-Sharkawi [8]; Lavee et al [9]; Proietti et al [10] Low frequency deficit irrigation (LFDI)…”
Section: Supplementary or Complementary Irrigationmentioning
confidence: 99%